An algorithm for estimation of membrane water content in PEM fuel cells - Gorgun, Haluk; Arcak, Murat; Barbir, Frano (ELSEVIER SCIENCE BV, 2006)
Available humidity sensing techniques are often intrusive, and of limited practical interest for real-time control applications due to their cost, size, and inadequate response time and accuracy. In this study, we present a novel method for estimation of PEM fuel cell humidity by exploiting its effect on cell resistive voltage drop. This voltage loss is discerned from mass transport, concentration, activation losses and open circuit voltage by a well-known fuel cell voltage model. The proposed scheme makes use of measurements of voltage, current, temperature, and total pressure values in the anode and cathode. It also incorporates dynamic estimators for hydrogen and oxygen partial pressures, adapted from [M. Arcak, H. Gorgun, L.M. Pedersen, S. Varigonda, A nonlinear observer design for fuel cell hydrogen estimation, IEEE Trans. Control Syst. Technol. 12 (1) (2004) 101-110]. The membrane resistance thus obtained is then used to estimate membrane water content following functional characterizations presented in [T.E. Springer, T.A. Zawodzinski, S. Gottesfeld, Polymer electrolyte fuel cell model, J. Electrochem. Soc. 138 (8) (1991) 2334-2342]. Experiments with this estimation technique, performed at the Connecticut Global Fuel Cell Center, are presented and discussed. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: PEM fuel cell; observer; estimation; drying; NONLINEAR OBSERVER DESIGN; DIAGNOSTIC-TOOL; MODEL; Chemistry; Electrochemistry; Energy & Fuels; Materials Science